Peningkatan Kemandirian Membaca Siswa Kelas V Melalui Metode Problem Based Learning di SDN 06 Pemudang - Sofia Sunya; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study was motivated by the issue of low reading independence among fifth-grade students at SDN 06 Pemudang, which often resulted in an unconducive classroom environment and low learning participation. The teacher had not yet applied a student-centered learning method, leading to suboptimal learning outcomes. The aim of this study was to determine the improvement in students’ reading independence through the application of the Problem Based Learning (PBL) method for Phase C fifth-grade students. This research used a Classroom Action Research (CAR) approach carried out in two cycles, each consisting of four stages: planning, implementation, evaluation, and reflection. The learning materials used were David the Leader and Solomon the Wise King. The research subjects were five fifth-grade students. Data collection techniques included observations to assess behavioral changes in the independence dimension and reading tests conducted at the end of each cycle. The data were analyzed using descriptive quantitative methods with percentage calculations. The results showed that the implementation of the PBL method successfully increased the character of independence as part of the Pancasila Student Profile (P3) dimension, from 70% in the first cycle to 92% in the second cycle. Student achievement in reading also improved significantly, with the “proficient” category increasing from 20% to 68%, and the “competent” category from 50% to 75%, while the “adequate” and “beginning to develop” categories dropped to 0%. The conclusion of this study is that learning using the Problem Based Learning method, when focused on a single Pancasila Student Profile dimension, can effectively enhance reading independence and learning achievement of fifth-grade Phase C students.